PERAN MIGRASI DALAM PROSES AKULTURASI DAN DAMPAKNYA TERHADAP TINGKAT HOMESICKNESS PADA MAHASISWA RANTAU - Joane Louis Lahasen Malau; Mirna Nur Alia Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2024)
The purpose of this research is to find out how migration can play a role in the acculturation process and cause homesickness in overseas students, to find out how acculturation can be a pressure for overseas students, and to find out how pressure and homesickness can affect students' mental state. The research method used is descriptive analysis with a qualitative approach, namely by collecting the sources needed for research studies then followed by analysis. The results of this study show that migration triggers an acculturation process that requires students to always adjust to cultural differences, norms, and values in their new environment. This process is not only a negative challenge for overseas students, but also brings opportunities for personal growth and intercultural skill development. This acculturation can have a significant impact on various aspects of life, ranging from emotional well-being, academic achievement, to social relationships. There is a need for tailored education, intervention and support strategies to support individuals in coping with the challenges and opportunities that arise during this process.